Kehujjahan Maslahah Mursalah Dalam Perspektif Imam Al-Ghazali Dan Najm Al-Din Al-Tufi - Arifin, Bustanul (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2024)
This study examines the authority of maslahah mursalah according to Imam Al-Ghazali and Najm al-Din al-Tufi, two scholars with differing views on applying the concept of public interest in Islamic law. Al-Ghazali is known for his conservative approach, while Al-Tufi is more flexible and progressive. The research uses the library research method. Data were collected from primary sources, namely the works of Al-Ghazali and Al-Tufi, as well as relevant secondary literature. Descriptive-qualitative and comparative analysis techniques were used to evaluate and compare the views of both scholars. The study found that Al-Ghazali requires maslahah to align with maqasid al-shariah and not contradict nash. Al-Tufi, on the other hand, emphasizes flexibility in prioritizing maslahah, especially when dealing with nash dzanni. Both scholars contribute significantly to the understanding and application of the concept of maslahah in contemporary Islamic law.